Critical evaluation of measured rotation–vibration transitions and an experimental dataset of energy levels of HD18O - Mikhailenko S. N. Semen Nikolaevich; Tashkun S. A.; Putilova T. A.; Starikova E. N.; Daumont L.; Jenouvrier A.; Fally S.; Carleer M.; Hermans C.; Vandaele A. C. (2009, 2009)
Title screen